2019
DOI: 10.21203/rs.2.13975/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary caregivers perceptions  of the role of fathers in the provision of nutritional care in a resource constrained environment in Cape Town, South Africa

Abstract: Background : The role of fathers has traditionally been defined as a breadwinner or provider, with men generally having lower levels of engagement in childcare tasks, especially with young children. The involvement of fathers has important consequences for child well-being, especially with regards to issues of diet/nutrition, exercise, play, and parenting behaviours. This paper seeks to explore the perceptions and limitations that primary caregivers have on fathers’ provision of care in a resource constrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Articles identified in the scoping review cited one or both of these norms in communities from Kenya (11), Ethiopia (12), Nepal (13,14), South Sudan (15), Ghana (16), India (17), and South Africa (18,19). In all circumstances, income poverty and food insecurity increased the severity of allocation inequities, with women acting as a 'buffer' (5) for the household in conditions under which food was unaffordable or otherwise difficult to access.…”
Section: Gendered Food Allocation Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Articles identified in the scoping review cited one or both of these norms in communities from Kenya (11), Ethiopia (12), Nepal (13,14), South Sudan (15), Ghana (16), India (17), and South Africa (18,19). In all circumstances, income poverty and food insecurity increased the severity of allocation inequities, with women acting as a 'buffer' (5) for the household in conditions under which food was unaffordable or otherwise difficult to access.…”
Section: Gendered Food Allocation Practicesmentioning
confidence: 99%
“…Multiple articles from the scoping review considered this paradigm, including studies from Ethiopia (34), China (35), South Africa (19,36), Kenya (37), and Malawi, as well as a cross-sectional study of Demographic and Healthy Survey data from 10 SSA 4 countries that found that, 'in general, likelihood of meeting recommended IYCF criteria was positively associated with the economic dimension of women's empowerment' (38). Two additional studies from SSA -Gilligan et al (39) (Uganda) and Bezner Kerr et al (40) (Malawi)-addressed women's bargaining power within an agricultural context, noting that increases in female autonomy with respect to smallholders' crop production decisions is associated with improved dietary diversity for children.…”
Section: Degree Of Maternal Autonomymentioning
confidence: 99%
See 3 more Smart Citations